The Effect of Fildar Fleiserman’s Model on the Achievement of Fifth-grade Literary Students in the Subject of History and the Development of Their Evaluative Thinking - Ghadeeb, Kamal Saleh (Journal of Tikrit University for Humanities, 2022)
The current research aims to identify the effect of Fildar Fleiserman’s model on the achievement of fifth-grade literary students in history and the development of their evaluative thinking. In Salah Al-Din Governorate, the researcher chose Al-Makassed High School for Boys intentionally. The research sample amounted to (69) students, including (35) students for the experimental group, and (34) students for the control group. The researcher made an equivalence between the two research groups in the variables (chronological age calculated in months and intelligence the previous year’s GPA, their evaluative thinking test, and the parents’ academic level). The research tool consisted of an achievement test consisting of (50) items, and their evaluative thinking test consisted of (20) questions, which are hypothetical attitudes in thinking. The validity and reliability of the two tools were confirmed. The results of the research indicated the superiority of the experimental group in the achievement test, and the presence of statistically significant differences in the evaluation-thinking test in favor of the students of the experimental group. In light of the research results, the researcher recommended a number of recommendations and suggestions.